Dental health status of adult population in Yemen (Thamar City) - Faraed D Salman; Khawla M Saleh; Aisha A Qasim (University of Mosul, College of Dentistry, 2006)
Aims: To evaluate the oral health status (dental caries, periodontal disease and treatment needs) in Yemenis adult individuals. Material and Methods: The sample included 471 individuals, age ranging between 20-59 years of both sexes using sharp dental caries explorers with WHO periodontal probes to detect periodontal health by the use of DMFT index of WHO (1997) and CPITN by WHO (1987). Results: The mean DMFT for the total sample was 7.33 + 0.3 which was increased with increasing age for the different age groups with a significant difference but no significant difference in the mean DMFT for total males and females has been found. The results also showed that the total number of teeth (880) with a mean of 1.81 tooth/person in need of treatment is the most prevalent needed one surface filling, and 581 teeth with a mean of 1.23 tooth/ person needed two or more surfaces filling. According to the highest CPITN there was significant difference between male and female in calculus at p < 0.05 and shallow pockets at p < 0.01. The results also revealed that the mean number of healthy sextants for the total sample was 4.13 while for bleeding and calculus were 1.02 and 0.21, respectively. It means that the treatment needs for periodontal disease is more toward oral hygiene procedure and prophylaxis. Conclusion: Dental health education program is an essential activity for promoting optimal oral health and preventing oral diseases